The relationship between job satisfaction, burnout, and turnover intention among physicians from urban state-owned medical institutions in Hubei, China: a cross-sectional study - Zhang, Yimin; Feng, Xueshan (BMC health services research, 2011)
Throughout China, a growing number of physicians are leaving or intending to depart from their organizations owing to job dissatisfaction. Little information is available about the role of occupational burnout in this association. We set out to analyze the relationship between job satisfaction, burnout, and turnover intention, and further to determine whether occupational burnout can serve as a mediator among Chinese physicians from urban state-owned medical institutions. A cross-sectional survey was carried out in March 2010 in Hubei Province, central China. The questionnaires assessed sociodemographic characteristics, job satisfaction, burnout, and turnover intention. The job satisfaction and occupational burnout instruments were obtained by modifying the Chinese Physicians' Job Satisfaction Questionnaire (CPJSQ) and the Chinese Maslach Burnout Inventory (CMBI), respectively. Such statistical methods as one-way ANOVA, Pearson correlation, GLM-univariate and structural equation modeling were used. Of the 1600 physicians surveyed, 1451 provided valid responses. The respondents had medium scores (3.18 +/-0.73) on turnover intention, in which there was significant difference among the groups from three urban areas with different development levels. Turnover intention, which significantly and negatively related to all job-satisfaction subscales, positively related to each subscale of burnout syndrome. Work environment satisfaction (b = -0.074, p < 0.01), job rewards satisfaction (b = -0.073, p < 0.01), organizational management satisfaction (b = -0.146, p < 0.01), and emotional exhaustion (b = 0.135, p < 0.01) were identified as significant direct predictors of the turnover intention of physicians, with 41.2% of the variance explained unitedly, under the control of sociodemographic variables, among which gender, age, and years of service were always significant. However, job-itself satisfaction no longer became significant, with the estimated parameter on job rewards satisfaction smaller after burnout syndrome variables were included. As congregated latent concepts, job satisfaction had both significant direct effects (gamma21 = -0.32, p < 0.01) and indirect effects (gamma11 × beta21 = -0.13, p < 0.01) through occupational burnout (62% explained) as a mediator on turnover intention (47% explained). Our study reveals that several, but not all dimensions of both job satisfaction and burnout syndrome are relevant factors affecting physicians' turnover intention, and there may be partial mediation effects of occupational burnout, mainly through emotional exhaustion, within the impact of job satisfaction on turnover intention. This suggests that enhancements in job satisfaction can be expected to reduce physicians' intentions to quit by the intermediary role of burnout as well as the direct path. It is hoped that these findings will offer some clues for health-sector managers to keep their physician resource motivated and stable.